Functional Responses of the Warehouse Pirate Bug Xylocoris flavipes (Reuter) (Hemiptera: Anthocoridae) on a Diet of Liposcelis decolor (Pearman) (Psocodea: Liposcelididae) - Augustine Bosomtwe; George Opit; Kristopher Giles; Brad Kard; Carla Goad (Insects)
Psocids are difficult to manage using grain protectants and phosphine hence research on non-chemical control methods. This study evaluated the effectiveness of Xylocoris flavipes (Reuter) (Hemiptera: Anthocoridae) at managing Liposcelis decolor (Pearman) (Psocodea: Liposcelididae). The functional responses of adult♀ and nymphs of X. flavipes on a diet of nymphs, adult♂, and adult♀ of L. decolor were determined under laboratory conditions at 28 ± 1 °C, 63 ± 5% RH, and a 0:24 (L:D) photoperiod. Maximum likelihood estimates (MLEs) of a logistic regression analysis showed that the functional responses of the life stages of X. flavipes on diets of three stages of L. decolor were Holling Type II. Estimates of the attack rate (a), handling time (Th), maximum predation (K) per day, and predation efficiency (η) per day for the two predator life stages against each prey life stage showed that the adult♀ X. flavipes predation rate was better compared with the nymphs. The adult♀ X. flavipes per capita consumption rate and searching efficiency were also higher than those of the nymphs. The data showed adults of L. decolor are more favorable for adult♀ X. flavipes whereas their nymphs prefer nymphs of L. decolor. Field evaluation of X. flavipes is required for their incorporation into psocid pest management.